2022
DOI: 10.1111/jcpt.13752
|View full text |Cite
|
Sign up to set email alerts
|

Effects of caregiver counselling on medication persistence and adherence in patients with dementia at a pharmacist‐managed clinic: A pilot study

Abstract: What Is Known and Objective Low treatment persistence and adherence in patients with dementia results in a rapid loss of disease control. This pilot study evaluated the impact of pharmacist‐provided caregiver counselling on treatment persistence, adherence, quality of life (QoL) in patients with dementia, as well as caregiver's knowledge of dementia, and caregiver burden. Methods This prospective, randomized controlled study was performed at a hospital‐based pharmacist‐managed clinic from December 2017 to Dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 94 publications
1
2
0
1
Order By: Relevance
“…This is in line with the previous study, which concluded that delivery via a caregiver was a major counselling barrier ( Albekairy, 2014 ). It is also in line with the findings of a recent study in Taiwan about the effect of caregiver counselling on medication persistence and adherence, which found no significant effect of caregiver intervention on treatment outcomes ( Huang et al, 2020 ).…”
Section: Discussionsupporting
confidence: 89%
“…This is in line with the previous study, which concluded that delivery via a caregiver was a major counselling barrier ( Albekairy, 2014 ). It is also in line with the findings of a recent study in Taiwan about the effect of caregiver counselling on medication persistence and adherence, which found no significant effect of caregiver intervention on treatment outcomes ( Huang et al, 2020 ).…”
Section: Discussionsupporting
confidence: 89%
“…Screaming and wailing is reported in 25% of AD patients, while aggressiveness violence is observed in 20% of patients with AD. The behavioral and mood disturba afflicting patients with AD are a major source of primary caregiver burden and an portant contributor to the decision to admit AD patients to institutionalized care [4,5] prevalence and severity of these disturbances are patient-specific [6]. Reported differe arise from the degree and location of brain damage, premorbid personality, the env ment and relationships with other people (Figure 2).…”
Section: Biochemical Diagnosis Of Alzheimer's Diseasementioning
confidence: 99%
“…Another psychologically interesting aspect of AD is the fact that symptoms and the rate at which they develop can be related to an individual's emotional response to the disease and the response of the patient's immediate environment, including significant people providing home care or institutional care and who are vulnerable to emotional burnout as a consequence [25,26]. A number of researchers indicate that AD symptoms, which can be described as heterogeneous and fluctuating, are influenced by the environment or aggravated by emotions expressed by the caregivers [4]. Therefore, psychological support 6 of 10 for caregivers becomes a challenge for the health and prevention policy implemented in Poland and beyond.…”
Section: Psychological Approach To Challenges Associated With Alzheim...mentioning
confidence: 99%
“…Na maioria dos casos de DA, são observados sintomas comportamentais e de humor, cuja prevalência é relatada da seguinte forma: 75% dos pacientes demonstram comportamento perturbador, associado à agitação; aproximadamente 60% exibem comportamento errante; e cerca de metade dos pacientes, apresentam sintomas depressivos, tais como anedonia, disforia, sentimentos de culpa, diminuição do apetite, perda de peso e dificuldade de concentração, além de uma propensão a vocalizações elevadas e ocorrência de sintomas psicóticos, como alucinações, delírios e paranoia. Manifestações de gritos e lamentos são mencionadas em aproximadamente 25% dos pacientes acometidos pela DA, ao passo que comportamentos agressivos e violentos são observados em cerca de 20% dos casos de DA (Huang et al, 2022).…”
Section: Introductionunclassified